Process for the enhanced preparation of high density monoatomic / diatomic catalysts in a stator-rotor reactor

CN122682618APending Publication Date: 2026-09-04HEBEI LEHENG CHEM EQUIP MFG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610792704.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-03
Publication Date
2026-09-04

AI Technical Summary

Technical Problem

[0006]本发明要解决的技术问题是提供一种利用定转子反应器强化制备高密度单/双原子催化剂的方法,该方法针对现有M-N-C单/双原子催化剂制备过程中存在的金属前驱体分布不均、局部富集、热解过程中易迁移团聚、活性位点密度受限等问题,利用定转子反应器强化前驱体构筑阶段的分散、混合和界面更新,有利于提高ZIF-8前驱体体系的分散均匀性,增加活性金属负载的有效面积;其次有利于金属前驱体在含氮碳源表面的均匀负载与稳定锚定,进而降低热解过程中的迁移和聚集,提高催化剂中活性位点密度和原子级分散比例,最终提升其在燃料电池阴极反应中的性能

Benefits of technology

[0023]本发明通过引入定转子反应器来强化活性金属负载,制备出高密度且分散均匀的M-N-C单/双原子催化剂,提高其在燃料电池中的应用性能。利用定转子反应器强化前驱体构筑阶段的分散、混合和界面更新,有利于提高ZIF-8前驱体体系的分散均匀性,增加活性金属负载的有效面积;其次有利于金属前驱体在含氮碳源表面的均匀负载与稳定锚定,进而降低热解过程中的迁移和聚集,提高催化剂中活性位点密度和原子级分散比例,最终提升其在燃料电池阴极反应中的性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122682618A_ABST
    Figure CN122682618A_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing high-density single / dual-atom catalysts by using a stator-rotor reactor, which comprises the following steps: adding a metal salt into a solvent; adding 2-methyl imidazole into the solvent; mixing the two solutions to react, centrifuging and washing to obtain ZIF-8 slurry; preparing a Tris buffer solution and dispersing the ZIF-8 slurry in the Tris buffer solution; adding dopamine hydrochloride into the ZIF-8 / Tris suspension; preparing a single / dual-metal-ligand complex solution and mixing the complex solution with the ZIF-8 coating solution; standing and aging, and then centrifuging, washing and drying; performing programmed temperature rising; and finally obtaining high-density active site single / dual-atom catalysts. The single / dual-atom catalysts prepared by the method can greatly improve the density of active sites, solve the problems of insufficient active sites and poor accessibility of single / dual-atom catalysts, and thus greatly improve the performance of the single / dual-atom catalysts in fuel cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of enhanced liquid-liquid mixing and mass transfer, specifically relating to a method for enhancing the preparation of high-density single / dual-atom catalysts using a stator-rotor reactor. Background Technology

[0002] The oxygen reduction reaction kinetics at the cathode of a hydrogen-oxygen fuel cell are slow, typically requiring a highly efficient catalyst to reduce overpotential and improve cell output performance. While existing commercial Pt-based catalysts exhibit high activity, they suffer from drawbacks such as high precious metal usage, high cost, and limited durability. Therefore, developing non-precious metal catalysts, particularly single / dual-atom catalysts with high-density active sites, has become an important research direction for fuel cell cathode catalytic materials. Anchoring metals in an atomically dispersed manner within a nitrogen-doped carbon framework is beneficial for improving metal atom utilization efficiency while balancing activity and cost-effectiveness.

[0003] Current methods for preparing MNC single / diatomic catalysts primarily involve stirring, impregnation, static complexation, and subsequent pyrolysis. While these methods can achieve precursor assembly on a laboratory scale, they often encounter problems in multi-component liquid-solid systems containing metal salts, ligands, MOF precursors, and polymeric coatings. These problems include easy agglomeration of solid particles, uneven local concentration distribution, limited mass transfer efficiency, and localized enrichment of metal precursors. These defects lead to the migration and aggregation of metal species during pyrolysis, resulting in metal particles or clusters, which is detrimental to the stable construction of high-density single / diatomic sites. Therefore, achieving efficient liquid-solid dispersion, rapid micro-mixing, and uniform interfacial contact during the precursor construction stage is crucial for obtaining high-density active sites.

[0004] Rotor-stator reactors offer significant process intensification advantages in liquid-liquid dispersion and reaction. These devices utilize the high-speed relative motion between the rotor and stator to generate strong shear, turbulence, and rapid interfacial renewal within a relatively small space. This allows for efficient dispersion of the two liquid phases before they enter the main reaction zone, forming numerous fine droplets and a large interphase contact area. Simultaneously, through the synergistic effect of functional zones such as the liquid film zone, dispersion zone, and packing zone, the two liquid phases continuously break down, disperse, collide, and remix during flow, effectively enhancing mass transfer and reaction processes in the liquid-liquid system.

[0005] For the preparation of high-density single / double atom catalysts, the precursor system usually involves the synergistic effect of multiple components such as metal salts, ligands, supports or polymer coatings. Metal species are prone to local enrichment and aggregation during precursor construction or subsequent heat treatment. Therefore, traditional preparation processes are difficult to achieve stable construction of high-density single / double atom sites. Summary of the Invention

[0006] The technical problem to be solved by this invention is to provide a method for enhancing the preparation of high-density single / dual-atom catalysts using a stator-rotor reactor. This method addresses the problems existing in the preparation of MNC single / dual-atom catalysts, such as uneven distribution of metal precursors, local enrichment, easy migration and aggregation during pyrolysis, and limited active site density. By utilizing a stator-rotor reactor to enhance the dispersion, mixing, and interface renewal during the precursor construction stage, this method is beneficial to improving the dispersion uniformity of the ZIF-8 precursor system and increasing the effective area of ​​active metal loading. Secondly, it is beneficial to the uniform loading and stable anchoring of metal precursors on the surface of nitrogen-containing carbon sources, thereby reducing migration and aggregation during pyrolysis, increasing the active site density and atomic-level dispersion ratio in the catalyst, and ultimately improving its performance in the cathode reaction of fuel cells.

[0007] To solve the first technical problem mentioned above, the present invention adopts the following technical solution: A method for enhancing the preparation of high-density single / dual-atom catalysts using a stator-rotor reactor includes the following steps: 1) Dissolve the zinc salt in a solvent, sonicate and stir to mix evenly to form metal salt solution A; 2) Dissolve the organic ligand 2-methylimidazole in a solvent, sonicate and stir to mix evenly to form ligand solution B; 3) Add ligand solution B to metal salt solution A and mix. Allow the mixture to react fully to form a reaction solution containing ZIF-8 precipitate. 4) The reaction solution containing ZIF-8 precipitate is centrifuged and washed to remove excess metal salt ions and organic ligands, forming a pure ZIF-8 slurry; 5) Disperse the ZIF-8 slurry in Tris buffer to obtain a uniform ZIF-8 / Tris suspension; 6) Add dopamine hydrochloride to the ZIF-8 / Tris suspension and coat ZIF-8 at room temperature with stirring to obtain a coated suspension; 7) The coated suspension is fed into a stator-rotor reactor and circulated at a certain speed for a period of time to allow dopamine hydrochloride to further polymerize and coat the ZIF-8 surface; 8) Metal salts are complexed with nitrogen-containing ligands to obtain mono / bimetallic ligand complex solutions; 9) Pass the mono / bimetallic ligand complex solution into the stator-rotor reactor and mix it with the coated suspension in step 7) to uniformly load the metal species and obtain the loaded mixture. 10) The loaded mixture was allowed to stand and age, then centrifuged, washed and dried to obtain a composite precursor containing metal, nitrogen source and carbon source; 11) The composite precursor obtained in step 10) is heat-treated in an inert atmosphere to finally obtain a high-density MNC single / double atom catalyst.

[0008] Preferably, in step 1), the zinc salt is one of zinc nitrate hexahydrate (Zn(NO3)2·6H2O), zinc chloride (ZnCl2), and zinc carbonate (ZnCO3); the solvent is one or more of anhydrous methanol, anhydrous ethanol, DMF, and isopropanol; and the concentration of the metal salt solution A is 50-500 mM.

[0009] Preferably, in step 2), the solvent is one or more of anhydrous methanol, anhydrous ethanol, DMF, and isopropanol; the concentration of the ligand solution B is 400-4000 mM.

[0010] Preferably, in step 3), the mixing method of solution A and solution B is one or more of stirring, microchannel, microwave, ultrasound, and hypergravity; the time for the full reaction is 2-24 h.

[0011] Preferably, in step 4), the centrifugation speed is 5000-12000 rpm; the washing is performed using deionized water, methanol, or ethanol.

[0012] Preferably, in step 5), the pH of the Tris buffer solution is 8.0-9.0, more preferably 8.5; the dispersion method includes one or more of stirring, sonication, and oscillation; the dispersion time is 10-60 min, more preferably 20-40 min.

[0013] Preferably, in step 6), the amount of dopamine hydrochloride added to the ZIF-8 / Tris suspension is 0.1-10 mg / mL, more preferably 1-5 mg / mL; the stirring time is 30-120 min.

[0014] Preferably, in step 7), the certain rotation speed refers to a rotation speed of 300-2800 rpm; the time period is 5-120 min.

[0015] Preferably, in step 8), the metal salt is one or more of iron salt, cobalt salt, manganese salt, copper salt, nickel salt, and chromium salt, more preferably one or more of sulfate, sulfite, nitrate, or chloride salt; the nitrogen-containing ligand is one or more of 1,10-phenanthroline, bipyridine, porphyrin, or their derivatives; and the molar ratio of the metal salt to the nitrogen-containing ligand is 0.01-20.

[0016] Preferably, in step 9), the mono / bimetallic ligand complex solution is introduced into the rotor reactor by continuous dripping, slow introduction, or segmented addition.

[0017] Preferably, in step 9), the rotor speed of the stator-rotor reactor is 400-2500 rpm, more preferably 600-2000 rpm; the mixing cycle time is 5-300 min.

[0018] Preferably, in step 10), the aging time is 1-3 h; the centrifugation speed is 8000-12000 rpm and the time is 5-20 min; the washing uses deionized water, ethanol or methanol; and the drying temperature is 60-80℃ and the time is 6-12 h.

[0019] Preferably, in step 11), the inert atmosphere is one of nitrogen, argon, and helium, the heat treatment temperature is 600-1150 ℃, and the heat treatment time is 1-5 h.

[0020] Any range described in this invention includes the endpoint, any value between the endpoints, and any subrange consisting of the endpoint or any value between the endpoints.

[0021] Unless otherwise specified, all raw materials used in this invention can be obtained commercially, and the equipment used in this invention can be conventional equipment in the relevant field or refer to existing technology in the relevant field.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] This invention enhances the loading of active metals by introducing a stator-rotor reactor, thereby preparing high-density and uniformly dispersed MNC single / dual-atom catalysts and improving their performance in fuel cells. Utilizing a stator-rotor reactor to enhance dispersion, mixing, and interface renewal during the precursor construction stage is beneficial for improving the dispersion uniformity of the ZIF-8 precursor system and increasing the effective area of ​​the active metal loading. Secondly, it facilitates the uniform loading and stable anchoring of the metal precursor on the nitrogen-containing carbon source surface, thereby reducing migration and aggregation during pyrolysis, increasing the density of active sites and the atomic-level dispersion ratio in the catalyst, and ultimately improving its performance in the fuel cell cathode reaction. Attached Figure Description

[0024] The specific embodiments of the present invention will be further described in detail below with reference to the accompanying drawings. Figure 1 The experimental flow chart of the present invention, which enhances the preparation of high-density single / dual-atom catalysts using a stator-rotor reactor, is shown. Figure 2 The EDS and aberration-corrected electron microscopy images of the high-density cobalt single-atom catalyst prepared in Example 1 of this invention are shown. Figure 3The LSV curve and PEMFC polarization curve of the high-density cobalt single-atom catalyst prepared in Example 1 of the present invention are shown. Figure 4 The EDS and aberration-corrected electron microscopy images of the high-density iron single-atom catalyst prepared in Example 2 of this invention are shown. Figure 5 The LSV curve and PEMFC polarization curve of the high-density iron single-atom catalyst prepared in Example 2 of the present invention are shown. Figure 6 The EDS and aberration-corrected electron microscopy images of the high-density iron-manganese diatomic catalyst prepared in Example 3 of the present invention are shown. Figure 7 The LSV curve and PEMFC polarization curve of the high-density iron-manganese diatomic catalyst prepared in Example 3 of the present invention are shown. Figure 8 The EDS and aberration-corrected electron microscopy images of the cobalt atom catalyst prepared in Comparative Example 1 of the present invention are shown. Figure 9 The LSV curve and PEMFC polarization curve of the cobalt single-atom catalyst prepared in Comparative Example 1 of the present invention are shown. Figure 10 The EDS and aberration-corrected electron microscopy images of the iron single-atom catalyst prepared in Comparative Example 2 of the present invention are shown. Figure 11 The LSV curve and PEMFC polarization curve of the iron single-atom catalyst prepared in Comparative Example 2 of the present invention are shown. Figure 12 The EDS and aberration-corrected electron microscopy images of the iron-manganese diatomic catalyst prepared in Comparative Example 3 of the present invention are shown. Figure 13 The LSV curve and PEMFC polarization curve of the iron-manganese dual single-atom catalyst prepared in Comparative Example 3 of the present invention are shown. Figure 14 This is an EDS diagram of the cobalt single-atom catalyst prepared in Comparative Example 4 of this invention; Figure 15 The LSV curve and PEMFC polarization curve of the cobalt single-atom catalyst prepared in Comparative Example 4 of this invention are shown. Figure 16 This is an EDS diagram of the iron single-atom catalyst prepared in Comparative Example 5 of this invention; Figure 17 The LSV curve and PEMFC polarization curve of the iron single-atom catalyst prepared in Comparative Example 5 of this invention are shown. Detailed Implementation

[0025] To more clearly illustrate the present invention, the following description, in conjunction with preferred embodiments, further clarifies the invention. Those skilled in the art should understand that the specific descriptions below are illustrative rather than restrictive, and should not be construed as limiting the scope of protection of the present invention.

[0026] See Figure 1 As shown, as one aspect of the present invention, a method for enhancing the preparation of high-density single / dual-atom catalysts using a stator-rotor reactor includes the following steps: 1) Dissolve the zinc salt in a solvent, sonicate and stir to mix evenly to form metal salt solution A; 2) Dissolve the organic ligand 2-methylimidazole in a solvent, sonicate and stir to mix evenly to form ligand solution B; 3) Add ligand solution B to metal salt solution A and mix. Allow the mixture to react fully to form a reaction solution containing ZIF-8 precipitate. 4) The reaction solution containing ZIF-8 precipitate is centrifuged and washed to remove excess metal salt ions and organic ligands, forming a pure ZIF-8 slurry; 5) Disperse the ZIF-8 slurry in Tris buffer to obtain a uniform ZIF-8 / Tris suspension; 6) Add dopamine hydrochloride to the ZIF-8 / Tris suspension and coat ZIF-8 at room temperature with stirring to obtain a coated suspension; 7) The coated suspension is fed into a stator-rotor reactor and circulated at a certain speed for a period of time to allow dopamine hydrochloride to further polymerize and coat the ZIF-8 surface; 8) Metal salts are complexed with nitrogen-containing ligands to obtain mono / bimetallic ligand complex solutions; 9) Pass the mono / bimetallic ligand complex solution into the stator-rotor reactor and mix it with the coated suspension in step 7) to uniformly load the metal species and obtain the loaded mixture. 10) The loaded mixture was allowed to stand and age, then centrifuged, washed and dried to obtain a composite precursor containing metal, nitrogen source and carbon source; 11) The composite precursor obtained in step 10) is heat-treated in an inert atmosphere to finally obtain a high-density MNC single / double atom catalyst.

[0027] The working principle of the preparation method of this invention is as follows: ZIF-8 is used as a porous framework precursor, and a polydopamine coating layer is used as a carbon and nitrogen source and a metal anchoring layer. Mono / bimetallic nitrogen-containing ligand complexes are introduced into the system. Utilizing the high shear and strong turbulence generated by the stator-rotor reactor, particle dispersion, interface renewal, and mass transfer processes are enhanced, resulting in more uniform polydopamine coating, more sufficient metal species loading, and more uniform distribution. Subsequently, after inert atmosphere heat treatment, the ZIF-8 framework and polydopamine layer are co-carbonized, and the nitrogen-containing ligands and metal species form a stable MN... x The coordination structure, along with the Zn volatilization-induced pore structure formation, effectively inhibits metal aggregation and increases the density of single / diatomic sites, ultimately yielding a high-density MNC single / diatomic catalyst.

[0028] According to certain embodiments of the present invention, in step 1), the zinc salt is one of zinc nitrate hexahydrate (Zn(NO3)2·6H2O), zinc chloride (ZnCl2), and zinc carbonate (ZnCO3); the solvent is one or more of anhydrous methanol, anhydrous ethanol, DMF, and isopropanol; and the concentration of the metal salt solution A is 50-500 mM.

[0029] According to certain embodiments of the present invention, in step 2), the solvent is one or more of anhydrous methanol, anhydrous ethanol, DMF, and isopropanol; the concentration of the ligand solution B is 400-4000 mM.

[0030] According to certain embodiments of the present invention, in step 3), the mixing method of solution A and solution B is one or more of stirring, microchannel, microwave, ultrasound, and hypergravity; the time for the full reaction is 2-24 h.

[0031] According to certain embodiments of the present invention, in step 4), the centrifugation speed is 5000-12000 rpm; the washing is performed using deionized water, methanol, or ethanol.

[0032] According to certain embodiments of the present invention, in step 5), the pH of the Tris buffer solution is 8.0-9.0, more preferably 8.5; the dispersion method includes one or more of stirring, sonication, and oscillation; the dispersion time is 10-60 min, more preferably 20-40 min.

[0033] According to certain embodiments of the present invention, in step 6), the amount of dopamine hydrochloride added to the ZIF-8 / Tris suspension is 0.1-10 mg / mL, more preferably 1-5 mg / mL; and the stirring time is 30-120 min.

[0034] According to some embodiments of the present invention, in step 7), the certain rotation speed refers to a rotation speed of 300-2800 rpm; the time period is 5-120 min.

[0035] According to certain embodiments of the present invention, in step 8), the metal salt is one or more of iron salt, cobalt salt, manganese salt, copper salt, nickel salt, and chromium salt, more preferably one or more of sulfate salt, sulfite salt, nitrate salt, or chloride salt; the nitrogen-containing ligand is one or more of 1,10-phenanthroline, bipyridine, porphyrin, or their derivatives; and the molar ratio of the metal salt to the nitrogen-containing ligand is 0.01-20.

[0036] According to certain embodiments of the present invention, in step 9), the mono / bimetallic-ligand complex solution is introduced into the rotor reactor by continuous dripping, slow introduction, or segmented addition.

[0037] According to some embodiments of the present invention, in step 9), the rotor speed of the stator-rotor reactor is 400-2500 rpm, more preferably 600-2000 rpm; the mixing cycle time is 5-300 min.

[0038] According to certain embodiments of the present invention, in step 10), the static aging time is 1-3 h; the centrifugation speed is 8000-12000 rpm and the time is 5-20 min; the washing uses deionized water, ethanol or methanol; the drying temperature is 60-80 ℃ and the time is 6-12 h.

[0039] According to certain embodiments of the present invention, in step 11), the inert atmosphere is one of nitrogen, argon, and helium, the heat treatment temperature is 600-1150 °C, and the heat treatment time is 1-5 h. Example 1

[0040] A method for enhancing the preparation of high-density Co-NC single-atom catalysts using a stator-rotor reactor includes the following steps: 1) Dissolve 2.976 g Zn(NO3)2·6H2O in 100 mL methanol, sonicate for 10 min and stir for 30 min to obtain metal salt solution A; 2) Dissolve 6.568 g of 2-methylimidazole in 100 mL of methanol, sonicate for 10 min and stir for 30 min to obtain ligand solution B; 3) Slowly pour ligand solution B into metal salt solution A and stir magnetically at room temperature for 6 h; 4) After the reaction is complete, centrifuge at 8000 rpm for 5 min, and wash with methanol 3 times to obtain ZIF-8 slurry; 5) Add 160 mL of deionized water to a beaker, add 0.242 g of Tris reagent, stir until completely dissolved, adjust the pH to 8.50 with 1 M HCl, and then bring the volume to 200 mL to obtain a 10 mM Tris buffer solution; disperse the obtained ZIF-8 slurry in the above 200 mL Tris buffer solution, sonicate in an ice bath for 20 min to obtain a uniform suspension; 6) Add 100 mg of dopamine hydrochloride to the homogeneous suspension and premix with magnetic stirring at room temperature for 5 min. 7) Pass the premixed suspension from step 6) into the stator-rotor reactor and circulate it at 500 rpm for 10 min; 8) Dissolve 50 mg of bipyridine in 50 mL of anhydrous methanol, stir for 10 min, add 25 mg of CoSO4·6H2O, and continue stirring at room temperature for 30 min to obtain a metal-ligand complex solution. 9) Slowly introduce the above metal-ligand complex solution into the stator-rotor reactor and continue to circulate for 30 min; after the reaction is completed, stop the reactor to obtain the loaded mixture; 10) Transfer the loaded mixture into a beaker and let it stand at room temperature for 1 h to age; centrifuge the aged mixture, wash it three times with deionized water and anhydrous ethanol, and dry it under vacuum at 60 °C to obtain the precursor. 11) The precursor obtained in step 10 was calcined under a nitrogen atmosphere, the room temperature was raised to 300 ℃ at a rate of 2 ℃ / min, and held for 1 h; then the temperature was raised from 350 ℃ to 900 ℃ at a rate of 5 ℃ / min and held for 1 h; after natural cooling, a high-density Co-NC single-atom catalyst was obtained.

[0041] Figure 2 EDS and aberration electron microscopy images of the high-density cobalt single-atom catalyst prepared in Example 1.

[0042] Figure 3 The LSV curve and PEMFC polarization curve of the high-density cobalt single-atom catalyst prepared in Example 1 show that its half-wave potential under acidic conditions is 0.75 V, and its peak power density reaches 0.53 W·cm⁻¹. -2 . Example 2

[0043] A method for enhancing the preparation of high-density Fe-NC single-atom catalysts using a stator-rotor reactor includes the following steps: 1) Prepare ZIF-8 slurry and 10 mM Tris buffer at pH 8.5 according to the method in Example 1; 2) Disperse the obtained ZIF-8 slurry in Tris buffer, sonicate on ice for 20 min, add 150 mg of dopamine hydrochloride to the suspension, and premix at room temperature for 5 min. 3) The suspension was fed into a stator-rotor reactor and circulated at 2000 rpm for 30 min to enhance the dispersion of ZIF-8 particles in the liquid phase and the initial deposition process of PDA. 4) Dissolve 60 mg of 1,10-phenanthroline in 50 mL of anhydrous methanol, stir for 10 min, add 35 mg of FeSO4·7H2O, stir at room temperature for 30 min to obtain a metal-ligand complex solution. 5) The Fe-Phen complex solution is continuously added to the stator-rotor reactor by dropwise addition over a period of 20 minutes, followed by a 60-minute circulation period after the addition is complete. This dropwise addition process allows for the simultaneous introduction of Fe precursors during PDA growth, thereby enhancing the synergistic anchoring between Fe species and the nitrogen-containing coating layer. 6) After the reaction, the slurry was transferred to a beaker and allowed to stand at room temperature for 2 hours to age. Then, it was centrifuged and washed with deionized water and anhydrous ethanol in sequence, and vacuum dried for 12 hours to obtain the composite precursor. 7) The precursor was subjected to heat treatment under a nitrogen atmosphere. The temperature was raised from room temperature to 350 °C at a rate of 2 °C / min and held for 2 h. Then the temperature was raised to 950 °C at a rate of 5 °C / min and held for 2 h. After natural cooling, a high-density Fe-NC single-atom catalyst was obtained.

[0044] Figure 4 EDS and aberration electron microscopy images of the high-density iron single-atom catalyst prepared in Example 2.

[0045] Figure 5 The LSV curves and PEMFC polarization curves of the high-density iron single-atom catalyst prepared in Example 2 show that its half-wave potential under acidic conditions is 0.8 V, and its peak power density reaches 0.83 W·cm⁻¹. -2 . Example 3

[0046] A method for enhancing the preparation of high-density Fe-Mn-NC diatomic catalysts using a stator-rotor reactor includes the following steps: 1) Prepare ZIF-8 slurry and Tris buffer according to the method in Example 1; 2) Disperse the obtained ZIF-8 slurry in Tris buffer, sonicate on ice for 30 min, add 150 mg of dopamine hydrochloride to the suspension, and premix at room temperature for 5 min. 3) The suspension was fed into a stator-rotor reactor and circulated at 2000 rpm for 30 min to enhance the dispersion of ZIF-8 particles in the liquid phase and the initial deposition process of PDA. 4) Dissolve 80 mg of 1,10-phenanthroline in 80 mL of anhydrous methanol, stir for 20 min, then add 35 mg of FeSO4·7H2O and 15 mg of MnSO4·4H2O, stir at room temperature for 30 min to prepare Fe / Mn bimetallic-ligand complex solution. 5) The complexing solution is continuously added to the stator-rotor reactor by dripping for 30 min, and the cycle continues for 60 min after the dripping is completed; 6) After the reaction, the slurry was transferred to a beaker and allowed to stand at room temperature for 2 hours to age. Then, it was centrifuged and washed with deionized water and anhydrous ethanol in sequence, and vacuum dried for 12 hours to obtain the composite precursor. 7) The precursor was subjected to heat treatment under a nitrogen atmosphere. The temperature was raised from room temperature to 350 °C at a rate of 2 °C / min and held for 2 h. Then the temperature was raised to 950 °C at a rate of 5 °C / min and held for 2 h. After natural cooling, a high-density Fe / Mn-NC diatomic catalyst was obtained.

[0047] Figure 6 EDS and aberration electron microscopy images of the high-density iron-manganese diatomic catalyst prepared in Example 3 of this invention.

[0048] Figure 7 The LSV curve and PEMFC polarization curve of the high-density iron-manganese diatomic catalyst prepared in Example 3 of this invention show that its half-wave potential under acidic conditions is 0.82 V, and its peak power density reaches 1.03 W·cm⁻¹. -2 . Comparative Example 1

[0049] Repeat Example 1, except that the stator-rotor reactor is replaced with a stirred reactor, and the Co metal is loaded by stirring with a paddle or magnetic stirring. The stirring speed is set to 500 rpm, and other operating conditions remain the same.

[0050] Figure 8 EDS and aberration-corrected electron microscopy images of the cobalt single-atom catalyst prepared for Comparative Example 1.

[0051] Figure 9 The LSV curve and PEMFC polarization curve of the cobalt single-atom catalyst prepared in Comparative Example 1 of this invention show that its half-wave potential under acidic conditions is 0.68 V, and its peak power density reaches 0.33 W·cm⁻¹. -2 .

[0052] Therefore, it can be concluded that using a stator-rotor reactor can increase the density of active sites in cobalt single-atom catalysts and improve their oxygen reduction performance. Comparative Example 2

[0053] Example 2 was repeated, except that: the ZIF-8 coating solution was poured into a stirred reactor and the stirring speed was set to 2000 rpm. Then, the Fe-Phen complex solution was added dropwise to the reactor over a period of 20 min. After the addition was completed, stirring was continued for 60 min. Other operating conditions remained the same.

[0054] Figure 10 EDS and aberration electron microscopy images of the iron single-atom catalyst prepared in Comparative Example 2.

[0055] Figure 11 The LSV curve and PEMFC polarization curve of the iron single-atom catalyst prepared in Comparative Example 2 of this invention show that its half-wave potential under acidic conditions is 0.76 V, and its peak power density reaches 0.69 W·cm⁻¹. -2 .

[0056] Therefore, it can be concluded that using a stator-rotor reactor can increase the density of active sites in iron single-atom catalysts and improve their oxygen reduction performance. Comparative Example 3

[0057] Repeat Example 3, except that the stator-rotor reactor is replaced with a stirred reactor, the stirring speed is set to 2000 rpm, and the Fe / Mn bimetallic-ligand complex solution is added dropwise to the reactor over a period of 30 min. After the addition is complete, stirring is continued for another 60 min, while keeping other operating conditions the same.

[0058] Figure 12 EDS and aberration electron microscopy images of the iron-manganese diatomic catalyst prepared in Comparative Example 3.

[0059] Figure 13 The LSV curve and PEMFC polarization curve of the iron-manganese diatomic catalyst prepared in Comparative Example 3 of this invention are shown. It can be seen that its half-wave potential under acidic conditions is 0.77 V, and its peak power density reaches 0.74 W·cm⁻¹. -2 .

[0060] Therefore, it can be concluded that using a stator-rotor reactor can increase the density of active sites in iron-manganese diatomic catalysts and improve their oxygen reduction performance. Comparative Example 4

[0061] Example 1 was repeated, except that dopamine hydrochloride was not added. Instead, the ZIF-8 / Tris suspension was directly introduced into the stator-rotor reactor, and the metal-ligand complex solution was introduced into the stator-rotor reactor for loading. Other operating conditions remained the same.

[0062] Figure 14 The image shows the EDS diagram of the cobalt single-atom catalyst prepared in Comparative Example 4.

[0063] Figure 15 The LSV curve and PEMFC polarization curve of the cobalt single-atom catalyst prepared in Comparative Example 4 show that its half-wave potential under acidic conditions is 0.71 V, and its peak power density reaches 0.43 W·cm⁻¹. -2 .

[0064] Therefore, it can be concluded that the absence of dopamine hydrochloride reduces the anchoring of the metal-ligand complex, decreases the loading of active metal, and thus weakens the performance of the fuel cell. Comparative Example 5

[0065] Example 2 was repeated, except that instead of preparing a metal-ligand complex solution, iron salts were directly added dropwise to the stator-rotor reactor for loading, while other operating conditions remained the same.

[0066] Figure 16 The image shows the EDS diagram of the iron single-atom catalyst prepared in Comparative Example 5.

[0067] Figure 17 The LSV curves and PEMFC polarization curves of the iron single-atom catalyst prepared in Comparative Example 5 show that its half-wave potential under acidic conditions is 0.74 V, and its peak power density reaches 0.75 W·cm⁻¹. -2 .

[0068] Therefore, it can be concluded that MN will not be pre-formed in the unprepared metal-ligand complex solution. x This reduces the loading density of metal active sites, thereby weakening the performance of the fuel cell.

[0069] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is impossible to exhaustively list all embodiments here. All obvious variations or modifications derived from the technical solutions of the present invention are still within the protection scope of the present invention.

Claims

1. A method for enhancing the preparation of high-density single / dual-atom catalysts using a stator-rotor reactor, characterized in that, Includes the following steps: 1) Dissolve the zinc salt in a solvent, sonicate and stir to mix evenly to form metal salt solution A; 2) Dissolve the organic ligand 2-methylimidazole in a solvent, sonicate and stir to mix evenly to form ligand solution B; 3) Add ligand solution B to metal salt solution A and mix. Allow the mixture to react fully to form a reaction solution containing ZIF-8 precipitate. 4) The reaction solution containing ZIF-8 precipitate is centrifuged and washed to remove excess metal salt ions and organic ligands, forming a pure ZIF-8 slurry; 5) Disperse the ZIF-8 slurry in Tris buffer to obtain a uniform ZIF-8 / Tris suspension; 6) Add dopamine hydrochloride to the ZIF-8 / Tris suspension and coat ZIF-8 at room temperature with stirring to obtain a coated suspension; 7) The coated suspension is fed into a stator-rotor reactor and circulated at a certain speed for a period of time to allow dopamine hydrochloride to further polymerize and coat the ZIF-8 surface; 8) Metal salts are complexed with nitrogen-containing ligands to obtain mono / bimetallic ligand complex solutions; 9) Pass the mono / bimetallic ligand complex solution into the stator-rotor reactor and mix it with the coated suspension in step 7) to uniformly load the metal species and obtain the loaded mixture. 10) The loaded mixture was allowed to stand and age, then centrifuged, washed and dried to obtain a composite precursor containing metal, nitrogen source and carbon source; 11) The composite precursor obtained in step 10) is heat-treated in an inert atmosphere to finally obtain a high-density MNC single / double atom catalyst.

2. The method for preparing high-density single / dual-atom catalysts according to claim 1, characterized in that: In step 1), the zinc salt is one of zinc nitrate hexahydrate (Zn(NO3)2·6H2O), zinc chloride (ZnCl2), and zinc carbonate (ZnCO3); the solvent is one or more of anhydrous methanol, anhydrous ethanol, DMF, and isopropanol; and the concentration of the metal salt solution A is 50-500 mM.

3. The method for preparing high-density single / dual-atom catalysts according to claim 1, characterized in that: In step 2), the solvent is one or more of anhydrous methanol, anhydrous ethanol, DMF, and isopropanol; the concentration of the ligand solution B is 400-4000 mM.

4. The method for preparing high-density single / dual-atom catalysts according to claim 1, characterized in that: In step 3), the mixing method of solution A and solution B is one or more of stirring, microchannel, microwave, ultrasound, and hypergravity; the time for the complete reaction is 2-24 h.

5. The method for preparing high-density single / dual-atom catalysts according to claim 1, characterized in that: In step 4), the centrifugation speed is 5000-12000 rpm; the washing is performed using deionized water, methanol, and ethanol.

6. The method for preparing high-density single / dual-atom catalysts according to claim 1, characterized in that: In step 5), the pH of the Tris buffer solution is 8.0-9.0, more preferably 8.5; the dispersion method includes one or more of stirring, sonication, and oscillation; the dispersion time is 10-60 min, more preferably 20-40 min.

7. The method for preparing high-density single / dual-atom catalysts according to claim 1, characterized in that: In step 6), the amount of dopamine hydrochloride added to the ZIF-8 / Tris suspension is 0.1-10 mg / mL, more preferably 1-5 mg / mL; the stirring time is 30-120 min.

8. The method for preparing high-density single / dual-atom catalysts according to claim 1, characterized in that: In step 7), the certain rotation speed refers to a rotation speed of 300-2800 rpm; the time period is 5-120 min.

9. The method for preparing high-density single / dual-atom catalysts according to claim 1, characterized in that: In step 8), the metal salt is one or more of iron salt, cobalt salt, manganese salt, copper salt, nickel salt, and chromium salt, more preferably one or more of sulfate salt, sulfite salt, nitrate salt, or chloride salt; the nitrogen-containing ligand is one or more of 1,10-phenanthroline, bipyridine, porphyrin, or their derivatives; and the molar ratio of the metal salt to the nitrogen-containing ligand is 0.01-20.

10. The method for preparing high-density single / dual-atom catalysts according to claim 1, characterized in that: In step 9), the mono / bimetallic ligand complex solution is introduced into the rotor reactor by continuous dripping, slow introduction, or segmented addition. Preferably, in step 9), the rotor speed of the stator-rotor reactor is 400-2500 rpm, more preferably 600-2000 rpm; the mixing cycle time is 5-300 min. Preferably, in step 10), the aging time is 1-3 hours; the centrifugation speed is 8000-12000 rpm and the time is 5-20 minutes; the washing uses deionized water, ethanol, or methanol; and the drying temperature is 60-80°C and the time is 6-12 hours. Preferably, in step 11), the inert atmosphere is one of nitrogen, argon, and helium, the heat treatment temperature is 600-1150 ℃, and the heat treatment time is 1-5 h.